Analysis of Pink Tourism From A Queer Criminology Perspective: The Dynamics of Perception and Stigma Experienced By Transpuan In Jakarta - Vion Patrick Putra Luwansa; Nadia Utami Larasati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Jakarta's rapid growth as an urban tourism hub has coincided with its quiet integration into the global